The pharmacokinetics of diclofenac and its interaction with sulfadoxine-trimethoprim in sheep - Alkac, Zeliha Keskin; Yerlikaya, Sevda Macin; Korkak, Fatih Ahmet; Tanyildizi, Sadettin; Hark, Betül Dagoglu; Dagoglu, Gürdal (Elsevier, 2023)
Objective: In this study, the pharmacokinetics of diclofenac was determined following a single intravenous and intramuscular administration of diclofenac alone and co-administration with sulfadoxine-trimethoprim in sheep. Study design: A randomized, controlled, experimental study. Animals: A total of 18 healthy male Ivesi sheep were used in the study (2-4 years old, with an average weight of 50 +/- 5 kg). Methods: Diclofenac was administered alone in the 1st group intramuscular (1 mg/kg), intravenous (1 mg/kg) in the 2nd group, and together (intramuscular diclofenac (1 mg/kg) and intravenous sulfadoxine-trimethoprim (5 mg/kg)) in the 3rd group. Blood was collected at 2, 5, 10, 15, 30, and 45 min and 1, 2, 3, 4, 5, 6, 7, 8, 10, 12, and 24 h following the administration. The plasma concentration of diclofenac was determined with high-performance liquid chromatography (HPLC). Pharmacokinetic parameters were analyzed using a non -compartmental analysis pharmacokinetic model. Results: The elimination half-life (t1/2), area under the plasma concentration-time curve (AUC), mean residence time (MRT), volume of distribution at steady-state (Vd), total body clearance (ClT), and bioavailability (F) values following the diclofenac were evaluated IM alone 2.31 +/- 0.01 h, 3.31 +/- 0.06 h* mu g/mL, 3.52 +/- 0.02 h, 0.96 +/- 0.02 L/kg, 0.28 +/- 0.00 mL/h/kg, 93%, respectively. When co-administered with sulfadoxine-trimethoprim the same kinetic values of diclofenac were 3.62 +/- 0.09 h, 3.52 +/- 0.05 h* mu g/mL, 5.54 +/- 0.46 h, 1.45 +/- 0.17 L/kg, 0.24 +/- 0.00 mL/h/kg and 99%, respectively. Sulfadoxine-trimethoprim increased the t1/2, AUC, MRT, Vd, and F values of diclofenac at statistically significant levels, and decreased the ClT value. Conclusions and clinical relevance: The results of the study indicate that the pharmacokinetics of diclofenac are altered when used with sulfadoxine-trimethoprim. Therefore, if the two drugs are used together, a new dose adjustment should be made for diclofenac.
Keywords: Diclofenac; Sulfadoxine; Trimethoprim; Sheep; Pharmacokinetics